2017
DOI: 10.1016/j.dyepig.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Changing optical nonlinearities of homoleptic bis(phthalocyaninato) rare earth praseodymium double-decker complexes by the redox reaction

Abstract: :We report the third-order nonlinear optical properties of the homoleptic bis(phthalocyaninato) rare earth double-decker complex Pr(OOPc) 2 (1), the oxidized species [Pr(OOPc) 2 ] + (2), and the reduced species [Pr(OOPc) 2 ] -(3), by performing the femtosecond-pulsed Z-scan experiments at the wavelength of 800 nm. It is found that the second-order hyperpolarizability in complex molecules decreases in the order of 1>2>3. More interestingly, the observed nonlinear absorption process changes from two-photon absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 48 publications
0
10
0
Order By: Relevance
“…Sheng and coworkers also tested a series of heteroleptic double-deckers [(OctO) 8 Pc]M(Pc) , M = Y, Ho, Er, Yb, and found that their σ 2PA is in the range of (126–183) × 10 3 GM, 467 which is still at the same level of M[(OctO) 8 Pc] 2 , M = Pr, Ce, Sm, and Lu series. 458–460…”
Section: Non-linear Optical Materials Based On Ree Sandwich Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sheng and coworkers also tested a series of heteroleptic double-deckers [(OctO) 8 Pc]M(Pc) , M = Y, Ho, Er, Yb, and found that their σ 2PA is in the range of (126–183) × 10 3 GM, 467 which is still at the same level of M[(OctO) 8 Pc] 2 , M = Pr, Ce, Sm, and Lu series. 458–460…”
Section: Non-linear Optical Materials Based On Ree Sandwich Complexesmentioning
confidence: 99%
“…Sheng and coworkers studied a series of homoleptic bis(phthalocyaninato) rare earth complexes M[(OctO) 8 Pc] 2 , M = Pr, Ce, Sm, and Lu. [458][459][460] The NLO performance of these compounds are tested using the exciting laser wavelength of 800 nm (Z-scan, 170 ns). The twophoton absorption cross-section s 2PA values of this series are in the range of (3-254) Â 10 3 GM, showing their strong nonlinear optical response.…”
Section: Third-order Nonlinear Optical Materialsmentioning
confidence: 99%
“…Macroheterocyclic tetraazoporphyrin ring complexes can be modied in such a way that the ligands interact with each other via coordination to transition metals and/or lanthanide ions, as is the case with multi-decker phthalocyaninato molecules. Such complexes are also referred to as advanced materials 1 and nd applications in many elds as single-molecule magnets, [2][3][4][5][6][7][8][9][10] sensors, [11][12][13] conductive materials, [14][15][16][17] optical limiters, [18][19][20][21][22][23][24][25][26][27][28] ambipolar organic eld-effect transistors, 29,30 supramolecular spin valves 31 and self-assembled nanostructures. 32,33 Lanthanide double-decker phthalocyanine (LnPc 2 ) complexes, in particular, have been the center of interest in research for a long time.…”
Section: Introductionmentioning
confidence: 99%
“…These NLO coefficients and cross-sections obtained for PBIPC are found to be superior in comparison with some of the recently reported phthalocyanine moieties making it an ideal candidate for probing its capability in applications such as (a) three-photon pumped (3PP) and frequency upconverted lasing (b) three-photon absorption (3PA) based optical power limiting and stabilization (c) 3PA-based bio-imaging by means of IR to visible conversion (d) data storage and others. [68][69][70][71] Fig . 7 Isodensity plots of FMOs and the energy values in eV by using the B3LYP method 6-31G (d,p) for PBIPC.…”
Section: Nonlinear Optical Studiesmentioning
confidence: 99%